IMPLEMENTING SUSTAINABLE DEVELOPMENT GOALS IN ZAMBIA: Realizing Women’s Access to State Land - Anthony Mushinge; Fahria Masum (African Journal on Land Policy and Geospatial Sciences, 2023)
Context and Background: